Incidence of Refeeding Syndrome in Pediatric Inpatients at the US–Mexico Border. Issue 6 (June 2021) - Gonzales, Victoria; Lodeiro, Carlos; Macias, Amanda; Francis, Denease; Gutierrez, Fatima; Pathak, Indu
Abstract : Objectives: Refeeding syndrome is a life-threatening, physiological process that occurs when patients with severe malnutrition are too rapidly rehabilitated, leading to the development of electrolyte abnormalities. Hypophosphatemia, a hallmark of the disease, has most commonly been studied, because it is recognized to result in cardiac arrhythmias, seizures, cardiac failure, respiratory failure, rhabdomyolysis, coma, and even death. Although many studies have found caloric intake to be a main causal factor in refeeding syndrome, few have explored other factors, such as geographic location. Border cities, such as El Paso, Texas, have a unique, diverse population. The purpose of this study was to establish the incidence of refeeding syndrome concentrated within a border city. Methods: We performed a retrospective chart review that focused on the incidence of refeeding syndrome in pediatric patients with eating disorders, ages 10 to 19 years, admitted to El Paso Children's Hospital, the only tertiary teaching hospital in the area, associated with Texas Tech University Health Science Center, located along the US–Mexico border, in El Paso, Texas. Results: Twenty-six subjects with a diagnosis of eating disorder were admitted to El Paso Children's Hospital for treatment between 2012 and 2019. Five subjects developed refeeding syndrome, recognized in our study as hypokalemia or hypomagnesemia, during their treatment. Conclusions: Among hospitalized adolescents admitted to El Paso Children's Hospital, 19% developed refeeding syndrome. This incidence was higher in our population than had been previously reported. Further research is needed to better establish a protocol for the treatment of patients with eating disorders. Abstract : The goal of this study was to determine the incidence of refeeding syndrome in pediatric patients admitted for eating disorders, specifically along the US–Mexico border. The majority of the authors' patients were Hispanic, with 19% developing refeeding syndrome. In this article, they discuss contributing factors unique to this population.